Mike’s Conker: a collaborative nonlinear knowledge elicitation repository for mobile HCI practitioners - Mohamedally, Dean; Edlich, Stefan; Zaphiris, Panayiotis; Petrie, Helen (My University, 2005)
In the field of Human Computer Interaction (HCI), we use a variety of Knowledge Elicitation (KE) techniques to capture user cognitive issues e.g. via interviews, paper prototyping, card sorting, focus group debates and more. MIKE (Mobile Interactive Knowledge Elicitation) is an ongoing research direction to enhance the KE capabilities of HCI practitioners via mobile and electronic methods. MIKE tools are a suite of Mobile HCI software and hardware configurations for a variety of mobile platforms. With MIKE's CONKER we describe a Collaborative Non-linear Knowledge Elicitation Repository for HCI practitioners. Its intention is to provide a scalable infrastructure for supporting the management and collaborative retrieval of mobile based KE datasets. Some of its functional design requirements include HCI practitioner profiles management, managing experimental progress from dispersed mobile HCI teams, timetabling expenditures for time critical empirical capture and participant management, and enabling concurrent HCI specialists to compare elicited mobile data. Further expansion of the CONKER system will include incorporation of distributed psychometric analysis methods. CONKER is realized as a sourceforge-alike Web-Portal using state-of-the art web-framework technologies. We describe several approaches to the capturing and management of HCI data and how CONKER makes this available to the HCI community.
Keywords: Mobile HCI; Mobile Interactive Knowledge Elicitation; Web-Portals